2016
DOI: 10.1111/jog.13021
|View full text |Cite
|
Sign up to set email alerts
|

Dual trigger with gonadotropin‐releasing hormone agonist and recombinant human chorionic gonadotropin improves in vitro fertilization outcome in gonadotropin‐releasing hormone antagonist cycles

Abstract: This novel and more physiological trigger approach using 500 μg leuprolide acetate plus 250 μg recombinant hCG may lead to an increase in the number of metaphase II oocytes, grade-A embryos, and may improve pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
(36 reference statements)
5
7
0
Order By: Relevance
“…In our study, the number of total embryos and grade 1 embryos was also significantly higher in women in the dual trigger group compared with those in the single trigger group. These findings are in keeping with those of Seval et al 21 who demonstrated that the mean number of grade‐A embryos was significantly higher in a dual trigger group than a single trigger group (1.6 ± 1.5 vs 1.1 ± 1.4, P =0.01), although the mean number of embryos obtained in their study differed from ours. This discrepancy may be due to differences in some of the criteria of the populations of the two studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the number of total embryos and grade 1 embryos was also significantly higher in women in the dual trigger group compared with those in the single trigger group. These findings are in keeping with those of Seval et al 21 who demonstrated that the mean number of grade‐A embryos was significantly higher in a dual trigger group than a single trigger group (1.6 ± 1.5 vs 1.1 ± 1.4, P =0.01), although the mean number of embryos obtained in their study differed from ours. This discrepancy may be due to differences in some of the criteria of the populations of the two studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that the mean number of metaphase II oocytes and retrieved oocytes among women of the dual trigger group was more than that of the single trigger group are supported by those of Seval and colleagues, 21 who found a significantly higher number of metaphase II and retrieved oocytes among women with dual trigger compared with those with single trigger. Similarly, Haas and colleagues demonstrated a significantly higher number of retrieved oocytes in PORs who received double triggering.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4 Hitherto, transabdominal ultrasound guided follicular aspiration for oocyte retrieval has still been used and presented in some case reports and original articles with small patient groups. 2,3,[6][7][8][9] Moreover, a good quality embryo and a healthy pregnancy were reported following transabdominal retrieval of follicles from heterotopically transplanted ovarian tissue by two different teams separately 10 However, the procedure is not well described in a systematic approach, and transabdominal oocyte retrieval using a "transvaginal probe" has not been reported thus far. In the first report transabdominal oocyte retrieval using ultrasound was performed with a full bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte retrieval was performed under inhalation anesthesia with intravenous propofol administration. Oocyte retrieval was performed 35–36 h after dual triggering method described by us before 9 when ≥1–2 follicles reached ≥18 mm in diameter with a double lumen oocyte retrieval needle (Cook Medical, Australia). All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional and/or national research committee (IRB (Institutional Review Board) (IRB No: 52044772‐840‐E‐458446) approval was obtained and with the 1964 Helsinki declaration and its later amendments or comparable ethical standards.…”
Section: Methodsmentioning
confidence: 99%